The Miranda ruling its past, present, and future - Wrightsman, Lawrence S.; Pitman, Mary L. (New York ; Oxford : Oxford University Press, 2010)
Where did Miranda go wrong? The purpose of this book is to identify and describe four problems with the implementation of the Miranda decision and to suggest remedies in order to have it achieve its original purpose.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Right to counsel -- United States; Confession (Law) -- United States; Police questioning -- United States; Miranda, Ernesto -- Trials, litigation, etc